2015
DOI: 10.1002/sce.21205
|View full text |Cite
|
Sign up to set email alerts
|

Social and Rational: The Presentation of Nature of Science and the Uptake of Change in Evolution Textbooks

Abstract: The nature of science (NOS) as described by education scholars is a critical component of scientific literacy and includes both rational and social aspects taught best in an explicit and reflective manner. NOS is frequently tied to a critical contextual empiricism (CCE) framework for knowledge production. Central to CCE is that objectivity is attained only with an integration of the rational and social within a diverse community of scholars that is open to criticism. The field of sexual selection theory is rip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 109 publications
(173 reference statements)
0
6
0
Order By: Relevance
“…Therefore, climate for individuals with these genders and orientations is not perceived as something that needs to be addressed ( Gibney, 2019 ). Similarly, studies on biology content have found that it is an instructor’s choices or their level of knowledge that maintains a predominantly “classic” view of sexual selection in biology classes and ignores changes within the discipline that promote more inclusive narratives ( Fuselier et al. , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, climate for individuals with these genders and orientations is not perceived as something that needs to be addressed ( Gibney, 2019 ). Similarly, studies on biology content have found that it is an instructor’s choices or their level of knowledge that maintains a predominantly “classic” view of sexual selection in biology classes and ignores changes within the discipline that promote more inclusive narratives ( Fuselier et al. , 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a primary goal of new educational standards is to teach students how scientists use models, rather than presenting immutable facts (AAAS 2011 ). This approach has been shown to be more effective and engaging than teaching facts (Fuselier et al 2016 ).…”
Section: Principle 4: Show the Iterative Process Of Sciencementioning
confidence: 99%
“…Lessons on sexual selection largely focus on the evolution of sex-associated traits and behavior in two superficially defined sexes (“males” and “females” in the present article). Generally, textbooks demonstrate the concept of “choosy females” versus “competing males” with a handful of highly sexually dimorphic species from few taxa—mostly mammals and birds (Fuselier et al 2016 )—and then provide students with a simplified model of sexual selection to explain these sex differences. The model, based on past work by Darwin ( 1871 , Darwin and Wallace 1958 ), Bateman ( 1948 ), and Trivers ( 1927 ), suggests that anisogamy leads to different potential rates of reproduction (PRR) in males and females, with males producing cheaper gametes and therefore having the ability to produce offspring more quickly; that differences in PRR lead to a biased operational sex ratio (OSR), with more males available for mating than females at any one time; and that the biased OSR drives mating competition among sperm producers and mate choice among egg producers.…”
mentioning
confidence: 99%
“…Built around the foundational feminist critiques of science forwarded by Harding and Haraway in the early 1990s, and the incorporation of community-engaged research approaches developed through CRES and Indigenous Studies (see for example Tallbear, 2013;Benjamin, 2013;Casumbal-Salazar, 2017;Liboiron 2019) our approach complements "critical contextual empiricism,"(CCE) as detailed by Fuselier, Jackson and Stoiko (2015). Building on the work of Helen Longino, the authors cite the origin of CCE in Longino's argument that "knowledge is inherently social because it is produced by communities, not individuals" (242).…”
Section: Approachmentioning
confidence: 99%